The role of radiography and MRI for eligibility assessment in DMOAD trials of knee OA - Roemer, Frank; Kwoh, C. Kent; Hayashi, Daichi; Felson, David T.; Guermazi, Ali (Nature Reviews Rheumatology, 2018)
Currently, no disease-modifying osteoarthritis drugs (DMOADs) have been approved. Past clinical trials have failed for several reasons, including the commonly applied definition of eligibility based on radiographic assessment of joint structure. In the context of precision medicine, finding the appropriate patient for a specific treatment approach will be of increasing relevance. Phenotypic stratification by use of imaging at the time of determining eligibility for clinical trials will be paramount and cannot be achieved using radiography alone. Furthermore, identification of joints at high risk of rapid progression of osteoarthritis is needed in order to enable a more efficient DMOAD trial design. In addition, joints at high risk of collapse need to be excluded at screening. The use of MRI might offer advantages over radiography in this context. Technological advances and simplified image assessment address many of the commonly perceived barriers to the application of MRI to assessment of eligibility for DMOAD clinical trials.
EVALuna2:35378